Problems of Social and Economic Optimization in Russia - TROSHIN, Alexander; STOLYAROVA, Vera; STOLYAROVA, Zlata; SANDU, Ivan; BOTASHEVA, Lydmila (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020DO - 10.14505/jarle.v11.2(48).34, 2020)
At the current stage of economic development, there is a lot of discussions about optimization policies, which have become widespread in both the industrial and sociocultural spheres. There are ambiguous positions on the justification of its application and various interpretations of the phenomenon itself, which balance in the corridor of polar opinions from categorically negative, to acceptable and necessary. Despite the fact that economic experts traditionally see optimization as a way to improve the efficiency of all management systems and, consequently, increase the competitiveness of the national economy, among the population the latest results of such a policy have been persistently rejected. Moreover, optimization is perceived by most people primitively, through simple cutback of the number of social institutions, merger of enterprises, monopoly threats that leads to job losses, on the one hand, and towards quality deterioration of goods and services, on the other hand. Meanwhile, optimization remains the key factor of the growth of the competitiveness of the economy in a global scale. Thus, it is necessary to investigate the phenomenon of optimization of the socio-economic sphere, to understand the reasons for the divergence of the concept itself and to analyze possible options for adapting the optimization strategy to modern Russian conditions.